Soil resistance and bulk density under different tillage system - Stošić, Miro; Brozović, Bojana; Vinković, Tomislav, agronom; Ravnjak, Boris; Kluz, Maciej; Zebec, Vladimir, agronom (2020)
A stationary field experiment of a reduced soil tillage was implemented at a Hypogley (Hypogleyic soils A–Gso–Gr soil horizon sequence) soil type of Eastern Croatia during three seasons and set up as a split-plot randomized block design in four repetitions. The tillage systems (TS) were as follows: 1) conventional tillage, i.e., plowing at 30 cm (CT), 2) disking up 10-12 cm (DT), 3) soil loosening up to 35 cm (LT), 4) no-tillage (NT). The experiment was designed to compare the penetration resistance (PR), soil moisture (SM), and bulk density (BD) at different TSs and soil depths. A cone penetrometer was used to measure the PR with 10 prods per TS, accompanied with a measurement of SM with a soil auger on every 10 cm, with four samples up to a 40-cm depth. The BD was determined by metal cylinders on every 10 cm up to a 30-cm depth, being weighed and dried thereafter to obtain an absolutely dry sample, and then calculated using absolutely a dry soil sample mass (m_s) and the soil volume (V). The PR and SM were significantly influenced by the TS and soil depth. The CT had the significantly lowest PR at all depths, while the DT has manifested a significantly higher PR at a soil depth amounting to 10 to 20 cm. The PR on NT were significantly diverse from the CT at all soil depths. The BD varied significantly concerning the TS and the soil depth. Subsequent to the three years, the CT had a significantly smaller BD at a depth amounting from 0 to 10 cm, and a significantly higher BD at 20- to 30-cm depth, compared to reduce the TS.
Stacionarni poljski pokus reducirane obrade tla proveden je u istočnoj Hrvatskoj na hipogleju tijekom triju sezona. Pokus je postavljen kao randomizirani blok-sustav u četiri ponavljanja. Sustavi obrade tla (TS) bili su sljedeći: 1) konvencionalna obrada tla oranjem na 30 cm (CT); 2) tanjuranje na 10–12 cm (DT); 3) rahljenje tla na 35 cm (LT); 4) no-tillage (NT). U eksperimentu su praćeni otpori tla (PR), vlaga tla (SM) i volumna gustoća tla (BD) na različitim TS-ovima i dubinama tla. Konusni penetrometar korišten je za mjerenje PR-a s 10 uboda po TS-u, praćeno sondiranjem za SM na svakih 10 cm, s četirima uzorcima do 40 cm dubine. BD je određen metalnim cilindrima na svakih 10 cm do 30 cm dubine. Izvagani uzorak je osušen do apsolutno suhoga uzorka, a zatim izračunan BD koristeći se apsolutno suhom masom uzorka tla (m_s) i volumena tla (V). PR i SM su bili pod značajnim utjecajem TS-a i dubine tla. CT je imao najniži PR na svim dubinama, DT je pokazao značajno veći PR na dubini tla od 10 do 20 cm u odnosu na CT. PR na NT bio je značajno različit od CT-a na svim dubinama tla. BD se znatno razlikovao po TS-u i dubini tla. Nakon tri godine CT je imao signifikantno manji BD na dubini 0-10 cm te signifikantno veći BD na dubini 20-30 cm u odnosu prema reduciranim sustavima obrade tla.
Bibliografija: 45 jed.
Summary ; Sažetak.
Keywords: Tlo -- Obrada tla -- Otpor tla -- Volumna gustoća tla -- Vlažnost tla